The Implementation of Cross-Sector Collaboration in Post-Mining Environmental Governance in Indonesia - Sahdan Mustari; Rifdan; Romansyah; Herman (Journal of Indonesian Scholars for Social Research, 2026)
Mining activities contribute significantly to the economy but often leave complex environmental impacts that require effective and sustainable post-mining management. Challenges in post-mining environmental governance in Indonesia often include company non-compliance, weak government oversight, and minimal community participation. These issues indicate the need for a cross-sectoral collaborative approach involving the government, the private sector, communities, and academics to achieve sustainable development goals. This study aims to analyze effective cross-sectoral collaboration models in post-mining environmental governance in Indonesia based on existing scientific literature, policies, and best practices. The research method used is a systematic literature review by examining various secondary data sources, including national and international journals, laws and regulations (such as Law No. 32 of 2009 concerning Environmental Protection and Management), research reports, and related policy documents. The collected data were analyzed qualitatively to identify patterns, barriers, enabling factors, and successful collaboration models implemented in similar contexts. The analysis shows that effective cross-sectoral collaboration requires a clear governance framework, equitable distribution of roles and responsibilities, and transparent conflict resolution mechanisms. Key factors for successful implementation include shared commitment, strong regulations, the availability of human and financial resources, and building trust between actors. The collaborative governance model has the potential to be an ideal approach for managing the complexity of post-mining environmental issues.